Analysis of adverse drug reactions encountered in a tertiary care hospital: a cross sectional study - F., Syed Hussain; V., Sathyanarayanan; R., Jamuna Rani (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adverse drug reactions are due to hazards of drug therapy and can occur with any class of drugs. The aim of this study was to evaluate and record adverse drug reactions reported from various departments of a tertiary care hospital. Methods: A Cross Sectional study conducted in a tertiary care hospital for a period of 4 months from March to June 2017 after Institutional Ethics Committee approval. ADRs reports collected and analyzed for causality, severity and preventability by international standardized scales. Results: A total of 38 ADR’s were reported during the study period with male predominance (58%). Most of the ADR’s (42%) were common in patients in the age group 19-39 years. More number of ADR’s were from Medicine (29%). Most commonly affected organ systems were skin (45%). The drugs mostly accounted were antibiotics (55%) especially Cephalosporins (33%). According to Naranjo’s causality assessment scale 74% of reactions were probable, 26% were possible, Modified Hartwig and Seigel severity assessment scale revealed 45% ADRs to be moderate, 42% were mild and 13% were severe, Modified Schumock and Thorton Preventability assessment scale which revealed 61% ADRs were not preventable, 32% were probably preventable,7% were definitively preventable. Conclusions: Adverse Drug Reactions are common and some of them resulted in increased healthcare cost due to need of some interventions and increased length of hospital stay. The health system should promote the spontaneous reporting of ADR’s. The proper documentation and periodic reporting to Pharmacovigilance Centres is required to ensure drug safety.